Simulation-based risk quantification: a reconciliation-based performance analysis. (3rd April 2017) - Freitas, Sandro; de Tomi, Giorgio; Marin, Tatiane; Rocha, Marcelo M.
Abstract: Recent studies have demonstrated the utilisation of stochastic simulation to quantify uncertainty in mineral deposits and allowing better management of the geological risk during mining scheduling. This paper describes an approach to evaluate the suitability of stochastically simulated models to characterise the real, but unknown, deposit represented in this study by an orebody model geostatistical estimate based on an extensive grade control drilling data-set. Traditional reconciliation techniques and the related mine call factors (or indicators) are evaluated against uncertainty measures derived from the set of stochastically simulated models. A case study carried out at the main mineral deposit of the Sossego copper mine in Brazil is presented in order to illustrate the practical aspects of the approach and how this approach is validated by traditional reconciliation studies using historical data of a mined out part of the orebody.